Attitude Of Students Towards E-Learning In Technical College Of ManagementBaghdad (Global Scientific Review, 2024)
The e-learning is now expected to become the new vector of higher and advanced education. The purpose of this study was to discover the attitude of students towards e-learning at TCMB in Baghdad by surveying 89 students of computer sciences. The survey methods were adopted for the present study, and a random sampling technique was used to sample the samples. Responses of students in the online survey indicate that the majority of students have positive views on e-learning.